Analisis Insiden Alat Angkut Material pada Area Hauling dengan Menggunakan Metode Bowtie di PT. XYZ Periode 2018-2020 - Deliani, Febby Fauzia; Wirawan, Mufti (UI Scholars Hub, 2021)
This study analyzes material transportation vehicle incidents in the hauling area of PT. XYZ from 2018 to 2020. Incidents are analyzed with bowtie method to identify risk factors or threat, preventive controls, consequences, escalation factors and controls. The purpose of this research is to analyze incidents in PT. XYZ using bowtie methods to further identifies which failures of barrier that allows incident to take place. This research is qualitative study by using incident investigation records as the unit analysis. The results of this study suggest the company to review procedures, standards, or methods used for preventive and mitigative controls and their risk identification document, conduct workload analysis on field supervisors, increase control and monitoring over human factors at work and improve the performance of preventive control’s technology.